AB0464 'real life' biological drug tapering results in few flares of disease and significant cost savings. (12th June 2018) - Batool, S.; Perry, M.; Russell, D.
Abstract : Background: The treatment of rheumatic diseases has been revolutionised in the biologic era. Remission and low disease activity are realistic targets. Several trials have suggested that dose reduction is achievable without loss of clinical effect. However, 'real life' response data is still lacking. Objectives: To increase interval dose of biologic drugs in a standard rheumatology clinic setting To assess the clinical response and determine potential cost savings Methods: Patients were identified by database interrogation and hospital prescription record, from a regional population of 4 00 000 over a 2 year period. All rheumatic conditions treated with anti-TNF and IL-6 blockers were potentially accepted for tapering. Those with low disease activity scores (RA and PsA DAS <2.1, AS BASDAI <4.1) for >1 year were screened and invited to consider dose reduction following discussion in a clinic. Results: 154 biologic patients were screened and 97 contacted to consider dose tapering. Of these, 40 patients agreed to participate in biologic dose reduction. Demographics: Mean age 51 years, 18 male patients and 22 females, concomitant MTX use in 49%. Diagnosis: RA-24, PsA −9, AS- 7. Drugs tapered included Adalimumab (28), Etanercept (5), Golimumab (5) and Tocilizumab (2). 8 patients flared during the programe and response was recaptured in 2 patients after increasing dose. 32 patients were successfully maintained on reduced dose with no requirement to date to increase dosing frequency. Biologic drug was completely withdrawn in 1 patient and 2 patients were commenced on reduced dose of DMARD. Prior to dose reduction mean DAS was 1.91 and mean BASDAI was 2.45. Low disease activity scores were recorded (mean DAS 2.1, mean BASDAI 2.6) post dose reduction (although incomplete data capture). Estimated cost savings are between 170, 000 EUR and 340000 EUR for the 2 years. Conclusions: Successful tapering of biologic drugs can be achieved and sustained in non-trial settings for patients with low disease activity. Significant cost savings have been confirmed with likelihood of recurrent savings over future years. Reference: [1] Edwards C, Fautrel B, Schulze-Koops H, Huizinga T, Kruger K. Dosing down with biologic therapies: a systematic review and clinicians' perspective2018. Acknowledgements: Ms Vandana Raghuvir Medical student at Glasgow University Disclosure of Interest: None declared